KEARIFAN LOKAL PETANI SAGU DESA SUNGAI TOHOR KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI PROVINSI RIAU - Santi Mulyani; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The background of this research is due to the importance of maintaining local wisdom to maintain the value of social capital values as well as maintaining mutual relations between humans and nature in the production process carried out collectively, for example in the management of traditional land and sago farming. The purpose of this study was to determine the existence of local wisdom in sago farming in Sungai Tohor Village. This research was conducted in Sungai Tohor Village, Tebing Tinggi Timur District, Kepulauan Meranti District. The population in this study was 64 sago farmers. The results of the study revealed that the existence of local wisdom in sago farming in Sungai Tohor Village was in the medium category as much as 67.19%, then those carrying out local wisdom in the low category were 17.19%, and those who were high in carrying out local wisdom up to this research data. only 15.63% of the 64 sago farmers were sampled. Factors that influence the existence of age and level of education. Keywords: Local Wisdom, Sago Farmers, Sungai Tohor